BLOGGING: A NEW PLATFORM FOR SPREADING RUMORS! - Hewa Majeed Zangana; Yuliana Isma Graha; Imad Fakhri Al-Shaikhli (CCIT Journal, 2015)
Blogs are a popular way to share personal journals, discuss matters of public opinion, pursue collaborative conversations, and aggregate content on similar topics. Blogs can be also used to disseminate new content and novel ideas to communities of interest. In this paper we present about the use of blogging in spreading rumors. Most blogs are interactive, allowing visitors to leave comments and even message to each other through widgets on the blogs and it is this interactivity that distinguishes them from other static websites. Topical content such as news and political commentary spreads quickly by the hour and then quickly disappears, while non-topical content such as music and entertainment propagates slowly over a much long period of time